Prediksi Kelas Tekstur Tanah Berdasarkan Karakteristik Topografi Menggunakan Analisis Diskriminan - Ade Setiawan; Mahfud Arifin (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2023)
This study aims to explain the influence of topographic attributes on soil texture classes using discriminant analysis. The topographic attributes considered in this study include elevation, slope, aspect, plan curvature, profile curvature, Topographic Wetness Index (TWI), and Topographic Position Index (TPI). The research location is the Sub Citarik Watershed, Upper Citarum Watershed, located at an altitude of 780-1800 m above sea level. The type of soil at the research location is Inceptisols. The results of the study show that topographic characteristics have a significant influence on soil texture classes. The discriminant analysis used in this study successfully classified soil texture classes with a reasonably high accuracy ((86,11%), although there is some room for improvement. This model shows good potential as a tool for predicting soil texture classes based on topographic characteristics, which can be used in various applications, including soil management and land use planning. The conclusion of this study highlights the importance of considering topographic attributes in soil management research and practice. Further research is suggested to improve the accuracy of the model and explore the use of this model in different contexts.